J. K. Rowling’s Harry Potter and the Order of the Phoenix: A Political Reading - Ali, Sabah Atallah Khalifa; Ismael, Zaid Ibrahim (Al-Adab Journal, 2019)
Like J. J. Tolkien’s Lord of the Rings and many other fantasies, Rowling’s Harry Potter is rich with allegorical implications that reflect the political anxiety of the era in which it was written. The critics and readers found connections between the events of the early parts of the novel and the historical havoc in world politics, like Hitler and World War II, a thing which Rowling attested in many of her interviews. Still, the texts are still open for other readings. It is possible to draw political parallels with contemporary issues. For instance, the American and British readers have been unable to resist identification with the events which mirror the international campaign on terrorism. This study is a political reading of Rowling’s Harry Potter and the Order of the Phoenix. It sheds light on the role of the Ministry of Magic in the novel and its relation to the governments’ policies to misguide the public about the terrorist threats to world powers, prior to the 2003 invasion of Iraq.